The Influence of Internal Control and GCG Implementation on Managerial Performance at PT Union Confectionery: Pengaruh Pengendalian Internal dan Penerapan GCG Terhadap Kinerja Manajerial pada PT Union Confectionery - Cindi Kosasi; Frenky Situmorang (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to determine the effect of internal control on managerial performance at PT Union Confectionery, to determine the implementation of GCG on managerial performance at PT Union Confectionery, to determine the effect of internal control and implementation of GCG on managerial performance at PT Union Confectionery. The research methodology used is quantitative research method. The type of data used in this study is quantitative data, namely data obtained in the form of numbers or figures. The data source is primary data. Primary data was obtained from the results of distributing questionnaires to employees of PT Union Confectionery. The population in this study is employees of PT Union Confectionery. From the population, a sample of 62 was selected. Validity test, reliability test, multiple linear regression analysis, classical assumption test, partial hypothesis test (T test) and simultaneous significance (F test), as well as determination coefficient test are all included in the data analysis and testing. The results of the analysis provide the equation Managerial Performance = 10.975 + 0.601 Internal Control + 0.148 Implementation of GCG + e. The t-test results show that the Internal Control variable has a positive and significant effect on Managerial Performance at PT Union Confectionery where tcount (3.231) > ttable (1.671), the GCG Implementation variable has a positive and significant effect on Managerial Performance at PT. Union Confectionery where tcount (1.826) > ttable (1.671), the F-test results show that Fcount (28.484) > Ftable (3.15) which means that the independent variables (Internal Control and GCG Implementation) simultaneously influence the dependent variable (Managerial Performance). The results of the coefficient of determination (R2) show that 49.1% of the Managerial Performance variable is influenced by Internal Control and GCG Implementation while the remaining 50.9% is influenced by other variables.